The Problematics of Simple Lawsuit Implementation To Reduce Civil Cases In Supreme Court - Bambang Sugeng; Zahry Vandawati Ch. (AL-HUKAMA, 2020)
This research has purpose to analyze the implementation of a simple lawsuit settlement to reduce the accumulation of civil cases in the Supreme Court. Also to analyze the constraints and obstacles in the application of simple claim resolution to reduce the buildup of civil cases and investigate the constraints and obstacles in the application of simple claim resolution to reduce the buildup of civil cases. This research is normative legal research that used the approach of statute approach and conceptual approach. The result of this research indicated that the implementation of simple lawsuit mechanismin court process could be quite helpful for citizen to settle the civil cases on state court with a quick process, simple system and low cost. In the context of implementing a simple lawsuit mechanism in court proceedings, there are several obstacles and have not maximally utilized in society, such as the minimum limit for the value of material claims is at most Rp. 200,000,000.00 (two hundred million rupiahs).